THE ROLE OF EXTRACURRICULAR WORK IN THE SYSTEM FORMATION OF COMMUNICATIVE CULTURE FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2022)
1п this article the author deals with the rôle of out-ofclass work in a higher educational establishment in the system of formingof future teachers’ communicative culture